Tropical fruit production through value chain development approach in Alamata Woreda, Northern Ethiopia: Experiences from IPMS - Berhane, G.; Gebrehiwot, A.; Gebrezgiabher, T.; Berhe, Kahsay; Hoekstra, Dirk (International Livestock Research Institute, 2010)
The Raya valley in Tigray, where Alamata Woreda is located, has suitable climate and rich water resources, among others, to grow various tropical fruits. Development of fruits only started a few years ago (1996) with the Raya Valley Development Project and the OoARD (Office of Agriculture and Rural Development), mostly focusing on papaya. A participatory rural appraisal (PRA) study conducted by the Woreda stakeholders identified tropical fruits as a potential marketable commodity in 2005. Using the commodity value chain approach, production, input supply and marketing problems, and opportunities were identified. Major problems were lack of knowledge and skills on tropical fruit production and management. Also, farmers were discouraged to grow fruits in their seasonally irrigated plots because of the free grazing which takes place during the dry season. Different extension approaches were used, including study tours to change the mind set of experts and farmers and to acquire knowledge. It also helped communities to devise organizational/institutional arrangements to protect seedlings, which encouraged the uptake of grafted mangoes and avocadoes. Most of the fruits can be sold locally, since most fruits so far were “imported” from other parts of the country. Some market linkages were also established in 2009 for the sale of the first grafted improved mango varieties. Farmer to farmer communications, trainings, workshops and media coverage facilitated the further dissemination of knowledge and skills between PAs (Peasant Associations) in Alamata and neighboring Woredas. Both women and men farmers benefited from the intervention. The household survey conducted in 2009 indicated that households involved in fruit production, on average, earned around Birr 1300 from the sale of fruits - 70 % from papaya. While in other Districts the development of improved marketable varieties was supported with the development of private nurseries, attempts to introduce them in Alamata did not succeed because of the presence of large scale regional nurseries, which grow a large number of seedlings and sale seedlings at a much reduced price to farmers.